47, XYY Syndrome and its Association with Male Infertility: Case Report - Prasad, Bheem; Parmar, Dinesh; Chander Sharma, Naresh (International Journal of Medical Research and Review, 2015)
47, XYY syndrome is one of the most common sex chromosomal anomaly found in humans after Klinfelter syndrome (47, XXY). It is frequently associated with infertility in males. This syndrome has an extra Y chromosome (XYY) due to non-disjunction of the Y chromosome in paternal meiotic II. The presence of an extra Y chromosome causes hormonal disbalance in the gonads that responsible for abnormal function of human chorionic gonadotropin. In the present study two cases of infertile men with severe oligozoospermia and azoospermia that also confirm by conventional cytogenetic analysis of the peripheral blood lymphocytes revealed the constitutional karyotype of 47, XYY. This report is likely to be helpful for counselling and early management of such infertile males.